Choice versus crisis: how Scotland could transform the way we think about prisons and punishment - Armstrong, Sarah (2009)
In late 2007, and in the face of a high imprisonment rate and unmitigated growth in the prison population over the past decade, Scotland’s Cabinet Secretary for Justice launched an independent commission to consider the use of imprisonment in Scotland and to raise the public profile of this issue. The Scottish Prisons Commission was Chaired by former Scottish First Minister, the Rt. Hon. Henry McLeish, and comprised a mixed group of criminal justice and civic leaders. The Commission reported in July 2008